I Only Say This Because I Love You: How The Way We Talk Can Make Or Break Family Relationships Throughout Our Lives - Deborah Tannen
Why does talk in families so often go in circles, leaving us tied up in knots? In this illuminating book, Deborah Tannen, the linguist and bestselling author of You Just Don't Understand and many other books, reveals why talking to family members is so often painful and problematic even when we're all adults.